Big data approaches in heart failure research - Lanzer, Jan David; Leuschner, Florian; Kramann, Rafael; Levinson, Rebecca T.; Sáez Rodríguez, Julio (Current heart failure reports, 2020)
The goal of this review is to summarize the state of big data analyses in the study of heart failure (HF). We discuss the use of big data in the HF space, focusing on “omics” and clinical data. We address some limitations of this data, as well as their future potential.